Application of Partial Hydrolysis of Virgin Coconut oil (VCO) on Carrageenan-based Edible Coatinng as (Sphyraena barracuda) Fishball Preservative during Room Storage - Erpiani Siregar; Jansen Silalahi; Dwi Suryanto (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2021)
Food spoilage during storage occurs physically, chemically and biologically which is related to the activity of bacteria. One of the natural preservation that is currently developing is the application of edible coating on perishable food, such as fishball. Addition of antibacterial agent is important to improve edible coating. Virgin coconut oil contains medium chain fatty acids which have antimicrobial properties, particularly monoglycerides and free fatty acids that produced by hydrolyzing partially triglycerides at the Sn-1 and Sn-3 position using Lipozyme. The aim of this research was to test the effect of edible coating carrageenan enriched with virgin coconut oil hydrolysis (HVCO) (concentrations 1%,3%,5%) on fishball quality.The method was an experimental with factorial completely randomized design.The samples were analyzed for sensorial assessments, Total plate Count, Total Volatile Base-Nitrogen, Water content, and pH for 5 days at room temperature. The study demonstrated that fish meatball coated with carrageenan based-edible coating fortified with HVCO showed the best result compared to controls (Uncoated fishball, coated without HVCO). Sensory attributes were still accepted by panelists until 3 days. Meanwhile, the same pattern depicted by TPC and TVB-N parameters. HVCO5% had inhibited microbial growth and retarded the increase of TVB-N number on fishball, the results were Log 5,08cfu/gr, 29,69 mg/100 gr respectively.